2007
DOI: 10.1093/hmg/ddm264
|View full text |Cite
|
Sign up to set email alerts
|

Lack of fibulin-3 causes early aging and herniation, but not macular degeneration in mice

Abstract: A mutation in the EFEMP1 gene causes Malattia Leventinese, an inherited macular degenerative disease with strong similarities to age-related macular degeneration. EFEMP1 encodes fibulin-3, an extracellular matrix protein of unknown function. To investigate its biological role, the murine Efemp1 gene was inactivated through targeted disruption. Efemp1(-/-) mice exhibited reduced reproductivity, and displayed an early onset of aging-associated phenotypes including reduced lifespan, decreased body mass, lordokyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
155
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 149 publications
(163 citation statements)
references
References 43 publications
7
155
0
1
Order By: Relevance
“…In mutated EFEMP1, an up-regulation of vascular endothelial growth factor (VEGF) expression is created by a protein misfolding that activates the unfolded protein response signaling pathway (14,15). Loss of EFEMP1, however, does not result in macular degeneration but in the appearance of hernias as a consequence of a reduction of elastic fibers of fascial connective tissue (16). Interestingly, when originally isolated in senescent fibroblasts, EFEMP1 was observed to be decreased by mitogenic culture conditions; however, when microinjected into fibroblasts, DNA synthesis was stimulated consistently in an autocrine and paracrine manner (17).…”
Section: Introductionmentioning
confidence: 99%
“…In mutated EFEMP1, an up-regulation of vascular endothelial growth factor (VEGF) expression is created by a protein misfolding that activates the unfolded protein response signaling pathway (14,15). Loss of EFEMP1, however, does not result in macular degeneration but in the appearance of hernias as a consequence of a reduction of elastic fibers of fascial connective tissue (16). Interestingly, when originally isolated in senescent fibroblasts, EFEMP1 was observed to be decreased by mitogenic culture conditions; however, when microinjected into fibroblasts, DNA synthesis was stimulated consistently in an autocrine and paracrine manner (17).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the human FBLN3 gene are associated with the eye diseases Doyne honeycomb retinal dystrophy and Malattia Leventinese (21). Fbln3-deficient mice show defective elastogenesis mainly in connective tissue fascia, leading to inguinal hernias and protrusion of xiphoid process without obvious manifestation in the vascular system (22). Developmental arteries and neural crest EGF-like protein (DANCE, also called FBLN5) is another member of the FBLN family, abundantly present in developing arteries (19,23).…”
mentioning
confidence: 99%
“…Among the seven known fibulins, fibulin-3 shares highest homology with fibulin-4 and -5. 19 -22 Recently, McLaughlin and colleagues 23 reported that fibulin-3 has a specific effect on the integrity of elastic fibers in fascial connective tissues. Fbln3 Ϫ/Ϫ mice develop early aging and herniation of the abdominal wall that increases progressively with age.…”
mentioning
confidence: 99%
“…Fbln3 Ϫ/Ϫ mice develop early aging and herniation of the abdominal wall that increases progressively with age. 23 In this study, we report the potential role of fibulin-3 in pelvic organ support by characterizing the gross and ultrastructural changes in the vaginal muscularis of mice deficient in fibulin-3 (Fbln3 Ϫ/Ϫ ). Further, studies were conducted to lend insight into potential mechanisms by which the lack of fibulin-3 led to pelvic organ prolapse.…”
mentioning
confidence: 99%